2015
DOI: 10.1038/ejcn.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the nutritional status between adult celiac patients on a long-term, strictly gluten-free diet and healthy subjects

Abstract: Our study demonstrates that a GFD is able to improve the nutritional status of celiac patients without inducing overweight or obesity. Our findings are related to a celiac population adopting a GFD based on a Mediterranean-type diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 28 publications
(44 reference statements)
5
78
0
1
Order By: Relevance
“…Concerning dietary fibers, Barone et al showed that CD patients consume less fibers compared to healthy adults. Similar findings were reached by other studies, both in adults and children [1,[4][5][6][7]. However, opposite findings were also reported [32][33][34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning dietary fibers, Barone et al showed that CD patients consume less fibers compared to healthy adults. Similar findings were reached by other studies, both in adults and children [1,[4][5][6][7]. However, opposite findings were also reported [32][33][34].…”
Section: Discussionsupporting
confidence: 90%
“…A gluten-free diet (GFD) is vital for patients with coeliac disease (CD). However, it has been described as potentially unhealthy due to the extensive presence of fat and calories [1][2][3][4][5][6][7][8]. This extensive intake can change body mass index (BMI) and modify lipid profiles, with mixed results indicating potential early atherosclerosis development in adults and children, but also improvements in high-density lipoprotein (HDL) levels [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This diet is safe and can reduce the long‐term risk of serious complications, both neoplastic and non‐neoplastic . A GFD is related to increased lipid and carbohydrate intake. Moreover, many adults and children with CD become overweight after treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Identifying genuinely wheat‐sensitive individuals is important because the gluten‐free diet has a number of potential disadvantages, including adverse effects on cardiovascular risk, higher rates of micronutrient deficiency, and even increased ingestion of toxins such as arsenic . That gluten avoidance improves weight control or general health is not supported by published evidence.…”
Section: Discussionmentioning
confidence: 99%